Exposure to stressful conditions alters the properties and fouling behavior of suspended microparticles in anaerobic processes. Issue 6 (December 2021) - Xu, Chenxiao; Li, Zicong; Wang, Jing; Zhou, Zhongbo
Abstract: Microparticles, a type of suspended particles in anaerobic membrane bioreactors (AnMBRs) with a size ranging from 0.45 to 10 µ m, play a vital role in fouling. Here, the occurrence, composition, and fouling behavior of microparticles were determined during the cultivation of anaerobic sludge under stressful conditions that included high sulfate (3 g/L), high ammonium (3 g/L), high temperature (55 °C), and high salinity (28 g NaCl/L) tests. The results showed that the total organics in the supernatant of anaerobic sludge liquor increased after exposure to high temperature and high salinity, and the proportion of microparticles decreased significantly compared with that of the control, which could be due to the decreasing ratios of live/dead cells in the microparticles, thereby producing more soluble organics (< 0.45 µ m). Accordingly, dead-end filtration tests showed that the supernatants with the same organic concentration in high temperature and high salinity groups had a decreasing fouling potential. Based on Hermia's model, the cake filtration model fitted the supernatant filtration data under all stressful conditions. Moreover, the high-temperature group also fitted well with the pore-blocking model. The correlation between fouling parameters and the microbial species of microparticles suggested the potential contributions of Bacteroidales, Aminicenantales, Anaerolineales, and Caldisericales to cake/gel fouling, and the positive effects of Ignavibacteriales and Syntrophobacterales on pore blocking. Overall, exposure to stressful conditions considerably altered the production and characteristics of microparticles during the anaerobic digestion, thus leading to different fouling mechanisms in AnMBRs. Graphical Abstract: ga1 Highlights: Stressful conditions greatly impacted formation and properties of micro-particles. High temperature and salinity led to a decreasing proportion of micro-particles. More dead cells and SMP formed under high temperature and salinity conditions. Pore blocking fouling was severer under high temperature and salinity conditions. Correlations between fouling and microbial species of micro-particles were built.